Different Doses of Intraumbilical Oxytocin on the Third Stage of Labor - Islamy, Nurul; Bernolian, Nuswil; BasiR, Firmansyah; Theodorus, Theodorus (Indonesian Journal of Obstetrics and Gynecology, 2018)
Objective: To compare the dose of oxytocin injected intraumbilicalltowards the duration of the third stage, blood loss volume, hemoglobinand hematocrit.   Methods: This study is a prospective randomised study with acontrol. The control group was given an intramuscular injection of10 IU oxytocin. The intervention of the three groups intraumbilicaloxytocin treatment dose of 10 IU, 20 IU and 30 IU diluted in 50 ml ofnormal saline solution and administered intraumbilically. Thesample selection by purposive sampling and the distribution groupbased on systematic random sampling (10 samples each). Data weretaken from the period April 2016-January 2017 with the inclusionand exclusion criteria. Data were analysed using Chi-square, T-test,ANOVA and Post hoc tests.   Results: Characteristics study for variables of age, occupation,parity, education, episiotomy and neonates weight showed homogeneouscharacteristics. The mean duration of the third stage forall groups was between 366.7  159.0 seconds and 440.1  244.99seconds. While the average number of postpartum haemorrhage forall group 61.894  226.3ml and 309.5  110.26 ml. There were nodifferences in the dose of oxytocin on the duration of the thirdstage (p> 0.05) and the amount of bleeding (p> 0.005). There was adifference of haemoglobin between intervention group of oxytocindose of 10 IU and 30 IU intraumbilical (p = 0.031). There was nodifference between the mean hematocrit levels between the groups(p> 0.005).   Conclusion: There were no differences in the dose of oxytocinintraumbilical towards the duration of the third stage, the amountof bleeding and hematocrit levels. The decrease of haemoglobingreater in 30 IU intraumbilical significantly. Keywords: duration of the third stage, haemoglobin and hematocrit,oxytocin intraumbilical, the amount of bleeding